MUSCULAR STRENGTH TRAINING IMPACTS IN YOUNG ATHLETES - Zhang,Kaiyuan (2023)
ABSTRACT Introduction: Muscle strength is directly related to its cross-sectional area and the volume of its fibers, but there is no absolute linear relationship between hypertrophy and improvement in athletic performance. Under this complex perspective, muscle training strategies have been implemented to promote relevant muscle strength and improve overall athletic ability. Objective: Explore the impacts of muscle strength training on young athletes based on sport kinetic principles. Methods: we adopted the method of intragroup statistical comparison with body indexes of 10 volunteers undergoing muscle training focused on the core and lower limb set. Results: Muscle strength gain was effectively verified via electromyogram, and the test of athletic skills showed an evolution in jumping, balance, and reduction of wrong passes. Conclusion: Evidence-based muscle training can increase muscle strength and promote sports skill gain in young athletes. Level of evidence II; Therapeutic studies - investigation of treatment results.